The effects of Shilajit on periodontal ligament cells in wound healing: a comprehensive in vitro study - Abdullah Alqarni; Jagadish Hosmani; Rayan Mohammedfarooq Meer; Abdulwahab Alqarni; Abdullah Alumudh; Elumalai Perumal; Mohmed Isaqali Karobari (BMC Complementary Medicine and Therapies)
Abstract Background Shilajit is a pale-brown to blackish-brown fluid that varies in consistency and is released from rock layers in various mountain ranges across the world. For thousands of years, traditional medical systems in several nations have included shilajit in one form or another as a rejuvenator and adaptogen. Numerous medicinal qualities have been attributed to it, several of which have been confirmed by contemporary scientific analysis. This in vitro study was established to investigate the effect of shilajit on human Periodontal ligament (hPDL) cell wound closure. Methods The cell viability was evaluated using the 3-(4,5-dimethylthiazol-2-yl)—2,5-diphenyltetrazolium bromide tetrazolium reduction (MTT) test following a 24-hour exposure of shilajit. With the use of an inverted phase contrast microscope, morphological alterations were noted. Acridine orange/ethidium bromide dual labeling, to evaluate the apoptotic cell death in shilajit treated cells. An in vitro wound healing test was utilized to evaluate wound healing in wounded hPDL cell monolayers for 24 h in the presence or absence of shilajit. The Matrix metalloproteinases-2 and 9 (MMP-2 and MMP-9) in hPDL cells treated with shilajit were measured using the enzyme-linked immunosorbent assay (ELISA) technique, and real-time PCR was used to examine gene expression linked to wound healing and apoptosis. Results Shilajit’s cytotoxicity evaluation on hPDL cells showed that dosages as high as 3 mg/mL had no adverse effects and maintains the cell viability, suggesting a possible stimulatory effect on cell growth. Cell viability was reduced significantly (p < 0.05) by dosages more than 4 mg/mL, indicating cytotoxicity at higher concentrations. According to the scratch wound healing assay, shilajit administration at doses of 2 and 3 mg/mL accelerated wound healing and improved cell migration in hPDL cells. Shilajit promoted a controlled inflammatory response and supported periodontal ligament healing by upregulating the expression of genes involved in collagen synthesis, collagen type I alpha 1 chain (COL1A1) and pro-inflammatory cytokines, tumor necrosis factor alpha (TNF-α) and, interleukin-1-beta (IL-1β), according to real-time PCR data. In addition, Shilajit raised the protein levels of MMP2 and MMP9, two important enzymes involved in tissue remodeling. Shilajit-treated hPDL cells showed a substantial increase of cell proliferation and no discernible apoptotic activity. Conclusions Our research offers novel proof that shilajit promotes hPDL cell migration and proliferation, which in turn promotes wound closure. According to these results, Shilajit may improve tissue regeneration, accelerate wound healing, and encourage the growth of periodontal ligament cells.